1987
DOI: 10.1093/clinids/9.supplement_5.s456
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Analysis of Bacterial Cytolysins

Abstract: Results of molecular and pathogenic studies of three different bacterial hemolysins (cytolysins) are presented. These exoproteins derive from the two gram-negative bacteria Escherichia coli and Aeromonas hydrophila and from the gram-positive pathogen Listeria monocytogenes. The hemolysin of E. coli is determined by an 8-kilobase (kb) region that includes four clustered genes (hlyC, hlyA, hlyB, and hlyD). This hemolysin determinant is part either of large transmissible plasmids or of the chromosome. The genes l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
1
1

Year Published

1989
1989
1995
1995

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 16 publications
1
12
1
1
Order By: Relevance
“…In contrast to other hemolysins and cytolysins (10,11,14), production of the enterohemolysin described here is associated with a temperate bacteriophage. Synthesis of enterohemolysin in E. coli JM83(pEO19) and its derivatives was found to be lethal for the bacterial host, which is in contrast to molecularly cloned a-hemolysin.…”
Section: Resultscontrasting
confidence: 71%
“…In contrast to other hemolysins and cytolysins (10,11,14), production of the enterohemolysin described here is associated with a temperate bacteriophage. Synthesis of enterohemolysin in E. coli JM83(pEO19) and its derivatives was found to be lethal for the bacterial host, which is in contrast to molecularly cloned a-hemolysin.…”
Section: Resultscontrasting
confidence: 71%
“…This property was localized to a segment of approximately 850 bp by deletion analysis. From the size of the region of DNA which encoded the hemolytic activity and the physiochemical properties of that hemolytic activity, it was apparent that the A44 plasmid did not encode the major 105-kDa hemolysin of A. pleuropneumoniae nor did it encode a hemolysin resembling other known hemolysins or toxins (3). To gain some insight into the nature of the A44-encoded hemolysin, the region conferring the hemolytic activity was sequenced.…”
Section: Resultsmentioning
confidence: 99%
“…Nicaud et al (21) have reported that HlyC activation involves neither phosphorylation nor glycosylation of HlyA. HlyA hemolytic and cytotoxic activity is sensitive to phospholipase and lipase treatment (3,4). However, it has not been established that HlyC activity involves either a covalent or noncovalent association of phospholipid to HlyA.…”
Section: Discussionmentioning
confidence: 99%